2023
DOI: 10.3390/foods12132585
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Honey—Evaluation of Quality and Stability during Storage

Abstract: Honey’s unique qualities should last for several years when properly stored. Therefore, it is up to manufacturers to choose the right shelf life for their product while also considering the product’s nature. Physicochemical parameters (water content, electrical conductivity, free acidity, pH, ash, water-insoluble matter, hydroxymethylfurfural (HMF), sugar content and composition, and diastase activity) were analyzed in 24 samples of sunflower honey collected from several localities in Vojvodina, Serbia. Crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Table 2 depicts the main physicochemical parameters of TCH. Honey is mostly composed of sugars [ 37 ]. The content of total reducing sugars was 74.74% (fructose content, 37.42%; glucose content, 37.32%), and sucrose content was 0.77%, all of which are in accordance with European Union honey standards [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 depicts the main physicochemical parameters of TCH. Honey is mostly composed of sugars [ 37 ]. The content of total reducing sugars was 74.74% (fructose content, 37.42%; glucose content, 37.32%), and sucrose content was 0.77%, all of which are in accordance with European Union honey standards [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is about 50-85% of the total mass of amino acids, and its concentration is different in different honeys [8]. The regulation defines the content of proline in honey, and it should not be less than 180 mg/kg [37]. The proline content of Jara honey samples is presented in Figure 10.…”
Section: 7mentioning
confidence: 99%
“…Active enzymes are very sensitive to high temperatures and will lose their activity when they exceed a certain temperature [36,37].…”
Section: The Activities Of Enzymes -mentioning
confidence: 99%
“…The storage conditions also influence the quality of honey. Živkov Baloš et al conducted a study to evaluate the quality and stability of sunflower honey during storage by analyzing its physicochemical parameters such as water content, HMF content, diastase activity, pH value, and free acidity [8]. The findings revealed that after being stored at room temperature for 18 months, there was a significant decrease in diastase activity but a notable increase in HMF content.…”
Section: Honey Quality Evaluationmentioning
confidence: 99%